The maze runner - Dashner, James, 1972- (London : The Chicken House, 2011)
Sixteen-year-old Thomas wakes up with no memory in the middle of a maze and realizes he must work with the community in which he finds himself if he is to escape.
Young Adult.
Young Adult
Keywords: Amnesia -- Juvenile fiction; Cooperativeness -- Juvenile fiction; Labyrinths -- Juvenile fiction; Amnesia -- Fiction; Cooperativeness -- Fiction; Labyrinths -- Fiction; Science fiction; Amnesia -- Fiction; Cooperativeness -- Fiction; Labyrinths -- Fiction; Science fiction; Science fiction